Pengaruh Problem Based Learning terhadap Pemahaman Membaca Siswa: Meta Analisis - Hatibie, Yunita (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
Most of previous research promotes Problem Based Learning to assist the students’ reading comprehension. It is need meta analysis research to review and to identify synthesise systematically on the effect of PBL towards the students’ reading comprehension. Therefore, the aim of this reseach is to combine results quantitatively from various similar independent studies to increase statistical power, provide a more precise estimate of the effect size, and resolve controversies stemming from conflicting research findings. This research used meta analysis quantitative with dicotomy data. Indeed, This is virtual and dekstop research that gain the data from journal and proceeding in google scholar, proceeding and Repository by using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) It was obtain 18 articles that reported the effect of PBL towards the students’ reading comprehention. But only 4 articles were included study and 14 articles were excluded study because of some criterian of this research. Total of partisipants are 226. Then the four articles were analyzed with quantitatif analysis to gain Fixed and Random effect size on Odds Rasio, Risk Rasio and Risk Difference by using RevMan (Review Manager) aplication to get Cochrane Reviews Standard and data syntesis on Forest Flot and Funnel Plot. Effect Estimate on Odds Ratio (M-H, Fixed, 95% CI) = 3.65 [1.94, 6.85, Heterogeneity I2=0%, P=0,45. Effect Estimate on Odds Ratio (M-H, Random, 95% CI) = 3.57 [1.88, 6.79], Heterogeneity I2=0%, P=0,45. Effect Estimate on Risk Ratio (M-H, Fixed, 95% CI) = 1.53 [1.24, 1.88], Heterogeneity I2=65%, P=0,04. Effect Estimate on Risk Ratio (M-H, Random, 95% CI) = 1.51 [1.04, 2.19], Heterogeneity I2=65%, P=0,04. Effect Estimate on Risk Differenciate (M-H, Fixed, 95% CI) = 0.25 [0.14, 0.36], Heterogeneity I2=65%, P=0,04.. Effect Estimate on Risk Differenciate (M-HRandom, 95% CI) = 0.24 [0.13, 0.36], Heterogeneity I2=14%, P=0,32. Based on Forest and Funnel Plot, it shown Problem Based Learning has significant effect towards the students’ reading comprehension.